Statins Improve Clinical Outcome After Non-aneurysmal Subarachnoid Hemorrhage: A Translational Insight From a Systematic Review of Experimental Studies - Kashefiolasl, Sepide; Wagner, Marlies; Brawanski, Nina; Seifert, Volker; Wanderer, Stefan; Andereggen, Lukas; Konczalla, Juergen (Frontiers in Neurology, 2021)
The efficacy of statin-treatment in aneurysmal subarachnoid hemorrhage (SAH) remains controversial. We aimed to investigate the effects of statin-treatment in non-aneurysmal (na)SAH in accordance with animal research data illustrating the pathophysiology of naSAH. We systematically searched PubMed using PRISMA-guidelines and selected experimental studies assessing the statin-effect on SAH. Analyzing our institutional database of naSAH patients between 1999-2018, statin-treatment (simvastatin 40mg/d), the occurrence of cerebral vasospasm (CVS), delayed infarction (DI), delayed cerebral ischemia (DCI) and clinical outcome were recorded. Among 18 titles, 13 studies used blood-injection-animal-model to assess the statin-effect in accordance with the pathophysiology of naSAH. All selected studies differ on study-setting concerning drug-administration, evaluation methods and neurological tests. Including 293 naSAH-patients, 51 patients with simvastatin-treatment were recruited for this analysis. Patients under treatment were affected by a significantly lower risk of CVS (p<0,01;OR3,7), DI (p<0,05;OR2,6), and DCI (p<0,05;OR3). Furthermore, there was a significant association between simvastatin-treatment and favorable-outcome (p<0,05;OR3). However, dividing patients with statin-treatment in pre-SAH (n=31) and post-SAH (n=20) treatment groups, we only detected a tenuous significant higher chance for favorable outcome (p<0,05; OR 0,05) in the small group of 20 patients with statin post-SAH treatment. Using a multivariate-analysis, we detected female gender (55%; p<0,001;OR4,9), Hunt&Hess ≤III at admission (p<0,002;OR4), no anticoagulant-therapy (p<0,0001;OR0,16), and statin-treatment (p<0,0001;OR24,2) as main factors improving the clinical outcome. Creating a translational concept, the statin-effect in naSAH-patients was confirmed in accordance with the pathophysiological background of experimental data focused on this field.